Productive strengthening of guinea pig breeders (Cavia porcellus) of the Colombian humid tropic (Revista Sistemas de Producción Agroecológicos, 2019)
The project was carried out in the humid tropical region, landscape of the Colombian Orinoquia, in Villavicencio, with the aim of generating a productive strengthening of guinea pig breeders (Cavia porcellus) from the design of an action plan for the improvement and associativity of producers, three main actions were carried out for this, the first a socioeconomic study of the families that expressed their interest in the commercial rearing of the animals which triggered in the second action, because with these results, 10 families were invited to develop a training plan on the good production practices of the guinea pig under Orinoquia conditions, training offered by the University of Los Llanos through the ECODER study group, using the constructivist method of learning by doing, in which method demonstration strategies, production activities and the business plan were developed, So that people will implement in their farms as productive units, these trainings are the preamble for the development of the organization of the producers, since the participating community was sensitized for the creation of an association of guinea pig producers in the Orinoquia, the which will be a pioneer in the production of this species, because it does not exist in the region. The producers have committed themselves by signing a letter of intent to advance the corresponding steps for the registration of the Association of Guinea Pig Producers before the Chamber of Commerce and to regulate the regulations to operate from an economic point of view and political organization, The main result that has been achieved within the project is the dissemination of guinea pig production, an increase in guinea pig production and the organization of producers to undertake collective processes that guarantee food security and family cash flow.
Keywords: guinea pig; productivity; community organization; rural development